ENHANCING FOUNDATIONAL LITERACY SKILLS THROUGH DIGITAL MEDIA: A CASE STUDY OF CANVA INTEGRATION AT ELEMENTARY SCHOOLS IN BIAK PAPUA - Rahmah Agustiani; Patma Tuasikal; Jelita Purnamasari (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This study examines the potential of the Canva application to enhance foundational literacy skills, specifically reading and writing, among elementary students in the East Biak District. The research was motivated by the lack of formal digital literacy training and limited digital resources, which hinder effective learning. The objective was to explore how active teacher facilitation and systematic training in Canva-based media can improve student engagement, collaborative interaction, and overall literacy outcomes. A qualitative descriptive methods approach was employed, involving direct classroom observations, structured interviews with school principals and teachers, and expert assessments of learning media designs. Observations indicated that schools with active teacher support achieved higher student engagement and fewer technical difficulties, while interview responses underscored the need for targeted training and resource enhancement. Expert assessments confirmed that well-designed digital media positively influenced reading comprehension and writing fluency. The findings suggest that integrating digital tools like Canva, coupled with effective teacher facilitation, is critical for improving foundational literacy skills, thereby advocating comprehensive digital literacy initiatives in schools.